Elicitation effect on cell biomass and production of alkaloids in cell suspension culture of the tropical tree Eurycoma longifolia - Keng, Chan Lai (2010)
The present study tests the effect of different elicitor on cell biomass and alkaloid production in Eurycoma longifolia cells. The cell suspension cultures were prepared by inoculating 0,5g FW (fresh weight) of cells obtained from first batch of suspension cultures prepared from callus in liquid MSBs medium. Different concentration of chitosan, NaH2PO4, Na2CO3 and polyvinylpyrrolidone (PVP) were added as elicitor to optimize cell biomass and alkaloid production. MSBs medium supplemented with100mg/L chitosan induced significant increment in the cell biomass while higher amount of chitosan (150mg/L) induced the highest production of 9-hydroxycanthin-6-one (0,44%) but not 9-methoxycanthin-6-one. The addition of 2mg/L and 20mg/L NaH2PO4 induced the highest increment in cell biomass and alkaloid production respectively. However, addition of different concentration Na2CO3 and polyvinylpyrrolidone showed inhibitory effect on cell growth with no significantly increased in alkaloid production.